Single-dose pharmacokinetics of ibrutinib in subjects with varying degrees of hepatic impairment*. Issue 1 (2nd January 2017) - de Jong, Jan; Skee, Donna; Hellemans, Peter; Jiao, James; de Vries, Ronald; Swerts, Dominique; Lawitz, Eric; Marbury, Thomas; Smith, William; Sukbuntherng, Juthamas; Mannaert, Erik
Abstract: This open-label, single-dose study was designed to characterize pharmacokinetics and safety profile of ibrutinib in hepatically impaired subjects. Each subject received single oral dose of ibrutinib (140 mg) following an overnight fast (hepatic impairment-mild [ n = 6], moderate [ n = 10], and severe [ n = 8]; healthy control [ n = 6]). Subjects with hepatic impairment showed significant increase in ibrutinib plasma exposures and fraction unbound ibrutinib. Compared to control group, mean exposure (AUClast; unbound ) in mild, moderate, and severe cohorts was 4.1-, 9.8-, 13.4-fold higher, respectively. Terminal half-life trended slightly longer in moderately and severely impaired subjects, but risk of accumulation on repeated dosing appears negligible as half-life did not exceed 10 h. Based on observed effects on exposure, reduced doses are recommended for patients with mild and moderate liver impairment (Child–Pugh Class A and B), whereas 140 mg is considered too high for severely impaired patients (Class-C). A single dose of 140 mg was well tolerated in this study (NCT01767948).